Syzygospora lapponica sp. nova (Syzygosporaceae, Heterobasidiomycetes) from Finland - Kotiranta, Heikki; Miettinen, Otto (Acta Mycologica, 2013)
A new Syzygospora species from Finland, S. lapponica is described and illustrated. The hitherto collections derive from Finnish Lapland and the species is apparently a mycoparasite of the rare old-growth forest dwelling polypore Antrodia infirma. The new species deviates from other species in the genus in having cylindrical, slightly bent spores and having a polypore as the host.